2018
DOI: 10.1111/ases.12662
|View full text |Cite
|
Sign up to set email alerts
|

Indocyanine green‐enhanced fluorescence‐guided video‐assisted axillary surgery for chronic lymphocele

Abstract: Introduction Lymphocele occurs frequently after regional lymph node dissection. Surgery with multiple lymphatic ligation represents the only reliable treatment for long‐standing chronic lymphocele. Materials and Surgical Technique We report the case of a man with chronic axillary seroma after axillary lymphadenectomy for melanoma. The lymphocele was unresponsive to conservative management and successfully treated with indocyanine green lymphography‐guided video‐assisted axillary surgery. Discussion Indocyanine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…The use of sclerosing agents for the management of seromas originate in the literature for treatment of pneumothorax and pleural effusions [2]. There are also various small scale case reports and studies describing this technique to treat seromas in various other areas of the body including abdomen, thigh, and breast to name a few [2,18,19]. A systemic review by Snood et al aimed to assess the literature on the use of sclerosants to treat seromas.…”
Section: Discussionmentioning
confidence: 99%
“…The use of sclerosing agents for the management of seromas originate in the literature for treatment of pneumothorax and pleural effusions [2]. There are also various small scale case reports and studies describing this technique to treat seromas in various other areas of the body including abdomen, thigh, and breast to name a few [2,18,19]. A systemic review by Snood et al aimed to assess the literature on the use of sclerosants to treat seromas.…”
Section: Discussionmentioning
confidence: 99%
“…Laparoscopic marsupialization is also an option 5 . To identify and embolize lymph leakage, lymphangiography using indocyanine green or ethiodized oil is effective 6,7 . A systematic review 8 showed proportions of successful interventions for percutaneous catheter drainage, percutaneous catheter drainage with the addition of sclerotherapy, and embolization: 0.612 (95% confidence interval [CI]: 0.490–0.722), 0.890 (95% CI: 0.781–0.948), and 0.922 (95% CI: 0.731–0.981), respectively.…”
Section: Discussionmentioning
confidence: 99%
“…13−18 Consequently, ICG may be an ideal diagnostic material for biomedical imaging. 19 During treatment by PDT, tumor tissue oxygen can be significantly depleted, leading to hypoxia. Hypoxia can cause poor responses in PDT and conventional procedures including radiotherapy and chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…It has fluorescence properties that can be used for imaging and can produce reactive oxygen species (ROS) for photodynamic therapy (PDT) and be induced by 808 nm laser irradiation to produce local hyperthermia for photothermal therapy (PTT). Moreover, ICG is inexpensive and widely available. Consequently, ICG may be an ideal diagnostic material for biomedical imaging . During treatment by PDT, tumor tissue oxygen can be significantly depleted, leading to hypoxia.…”
Section: Introductionmentioning
confidence: 99%